2021
DOI: 10.1101/2021.06.17.448482
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Development of a semi-automated method for tumor budding assessment in colorectal cancer and comparison with manual methods

Abstract: Tumor budding is an established prognostic feature in multiple cancers but routine assessment has not yet been incorporated into clinical pathology practice. Recent efforts to standardize and automate assessment have shifted away from haematoxylin and eosin (H&E)-stained images towards cytokeratin (CK) immunohistochemistry. In this study, we compare established manual H&E and cytokeratin budding assessment methods with a new, semi-automated approach built within the QuPath open-source software. We appl… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…As such, the results of this study should serve more as a stepping stone for a deep-learning digital-pathology approach in a larger cohort. Several deep-learning models already exist for the automated detection and classification of individual markers, for instance peritumoural budding [43], TIL density [44], and the fibrotic stroma type [45]. Additionally, studies have shown deep-learning on histopathology capable of predicting relevant outcomes in a hypothesisfree manner, i.e., not training the model to predict specific markers but instead let the model identify relevant features itself for accurate prediction of the outcome of interest.…”
Section: Discussionmentioning
confidence: 99%
“…As such, the results of this study should serve more as a stepping stone for a deep-learning digital-pathology approach in a larger cohort. Several deep-learning models already exist for the automated detection and classification of individual markers, for instance peritumoural budding [43], TIL density [44], and the fibrotic stroma type [45]. Additionally, studies have shown deep-learning on histopathology capable of predicting relevant outcomes in a hypothesisfree manner, i.e., not training the model to predict specific markers but instead let the model identify relevant features itself for accurate prediction of the outcome of interest.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, IHC is frequently used to help pathologists identify tumor buds (TB) [2]. Several studies involving experienced gastrointestinal pathologists have reported on the prognostic value of TB based on H&E staining, as well as on IHC [3][4][5]. At the same time, moderate to substantial inter-observer variability has been reported for TB scoring both in H&E and IHC, including our recent work [6].…”
Section: Introductionmentioning
confidence: 85%
“…Within these ROIs, tumor bud detection is achieved using classical image analysis operations, sometimes in combination with some form of machine learning. Fischer et al [4] use QuPath software to classify tumor buds in digitized CRC tissue microarrays (TMA) based on color and measured cluster size (area instead of nuclei number) and compare the results with manually obtained tumor buds yields in H&E and CK per count and in a bud-by-bud fashion. They analyze the impact of all methods on patient survival.…”
Section: Related Workmentioning
confidence: 99%